CORRELATION BETWEEN THE SITUATION; SIZE, AND HISTOLOGICAL TYPE BREAST CANCER AND LEARNED NUMBER OF LYMPH NODES - Aviño, J. (2015)
In the study of 95 women operated on for breast cancer in our department we see as the tumor grows, there is a greater number of lymph nodes affected: 37.7% in stage T3 and T4; 16.1% in stage T and 2.97% in stage T1, even if the surgical removal of lymph nodes overall number that was similar in the various stages. The number of lymph nodes removed was greater when more undifferentiated tumor was. The average of excised lymph nodes was greater than 15. The most common histological type is the type infiltrating ductal carcinoma NOS. Regarding tumor localization, are tumors of central origin can give a greater number of lymph nodes. The higher number of cancers was found in outer quadrants, which also had the largest number of axillary lymph nodes.